Does Firm Size, Firm Age, Leverage, Profitability and Tax Planning Affect Earnings Management? - Chamalinda, Khy'sh Nusri Leapatra (Jurnal Akuntansi, Manajemen dan Ekonomi, 2023)
This reseacrh aims to analyze and determine the effect of firm size, firm age, leverage, profitability, and tax planning on earnings management. The independent variables used are firm size, firm age, leverage, profitability, and tax planning. The dependent variable used is earnings management. The population in this research are companies in the consumer non-cyclicals sector that are listed on the Indonesia Stock Exchange (IDX) in 2018-2021. The sampling technique was carried out by purposive sampling technique. The sample of this research is 27 companies that meet the sample criteria. The data analysis used is multiple linear regression. The results of this research indicate that firm size has an effect on earnings management. Profitability has a negative effect on earnings management. Firm age, leverage, and tax planning have no effect on earnings management.